2017
DOI: 10.1109/tap.2017.2670503
|View full text |Cite
|
Sign up to set email alerts
|

Exciting Vorticity Through Higher Order Bessel Beams With a Radial-Line Slot-Array Antenna

Abstract: International audienceIn this communication, it is shown that a nondiffracting vortex beam (i.e., a higher order Bessel beam with azimuthal phase variation) can be generated in the near field by synthesizing an inward cylindrical traveling-wave distribution over a finite aperture antenna. A radial line slot array (RLSA) is then designed to prove the concept. The collimated vortex beam is excited in the proximity of the RLSA, within a region properly defined by the nondiffracting range of the generated beam. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…[2][3][4] In optical domain, Bessel beam is generated by using the spatial light modulator, the circular slit, the axicon, and the hologram. [5][6][7][8] The spatial light modulator system is complex to realize. The circular slit and the axicon are very simple.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In optical domain, Bessel beam is generated by using the spatial light modulator, the circular slit, the axicon, and the hologram. [5][6][7][8] The spatial light modulator system is complex to realize. The circular slit and the axicon are very simple.…”
Section: Introductionmentioning
confidence: 99%
“…ELICAL beams (HB) and the associated beam property referred to as Orbital Angular Momentum (OAM) [1] have generated considerable interest [2] in recent years and in consequence a wide diversity of proposals for so-called OAM antennas has appeared in the engineering and science literature, mostly over the last decade [3][4][5][6][7][8][9][10][11][12]. It has been mathematically demonstrated that communication range using a pair of transmit-receive OAM antennas will be limited, for example in [13] where link transmittance was derived as a function of distance and helical mode index.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has recently been shown that Bessel beams can conveniently be generated using inward cylindrical waves only [15][16][17], thus leading to the design of wideband radiators. (Note that in [15] analytical results are obtained for zeroth-order Bessel beams, whereas in [17] numerical results are extended to higher orders.) Even more interestingly, in [18] this principle has been successfully used to design a sinusoidally-modulated LWA based on the excitation of a backward leaky wave.…”
Section: Introductionmentioning
confidence: 99%